Diagnostic challenges in supraventricular tachycardia: anticipating value of natriuretic peptides - Yetkin, Ertan (Cardiovasc Endocrinol Metab, 2018)
It is important not to overlook supraventricular tachycardia (SVT) in patients complaining of palpitation or tachycardia-related symptoms but with normal ECG and heart rate in emergency department or outpatient clinics. The severity and presentation of symptoms is highly variable and depends on features including heart rate, duration of tachycardia, underlying heart disease, and individual patient perception. Early measurement of natriuretic peptides in patients presenting with palpitation and/or tachycardia-related symptoms would guide the clinician to rule out tachycardia and/or SVT. High levels of natriuretic peptides within 30 min of postattack period would certainly increase the likelihood of SVT.